2023
DOI: 10.1101/2023.01.12.523822
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Z-Flipon Variants reveal the many roles of Z-DNA and Z-RNA in health and disease

Abstract: Identifying roles for Z-flipons remains challenging given their dynamic nature. Here we perform genome-wide interrogation with the DNABERT transformer algorithm trained on experimentally identified Z-DNA sequences. We show Z-flipons are enriched in promoters and telomeres and overlap quantitative trait loci for RNA expression, RNA editing, splicing and disease associated variants. Surprisingly, many effects are mediated through Z-RNA formation. We describe Z-RNA motifs present in SCARF2, SMAD1 and CACNA1 trans… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…In line with our previous studies 23,26,27 we observed enrichment of Z-flipons in promoters. The result for Z-forming sequences in CpG-promoters is unsurprising as alternating d(CG) d(C1-3G1-3) where the cytosines are in the anti-conformation (as in B-DNA), are prone to Z-DNA formation.…”
Section: Conserved Patterns Of Transcription Factors Regulators and H...supporting
confidence: 93%
See 1 more Smart Citation
“…In line with our previous studies 23,26,27 we observed enrichment of Z-flipons in promoters. The result for Z-forming sequences in CpG-promoters is unsurprising as alternating d(CG) d(C1-3G1-3) where the cytosines are in the anti-conformation (as in B-DNA), are prone to Z-DNA formation.…”
Section: Conserved Patterns Of Transcription Factors Regulators and H...supporting
confidence: 93%
“…As it was shown by us and others based on sequence analysis alone ( 18,19,24,27,35,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) ), Zflipons are enriched in promoters. Here we find Z-flipon enrichment in conserved humanmouse sequences is even higher and we found common pattern of omics features colocalized with conserved Z-flipons at bidirectional promoters.…”
Section: Z-flipons Enrichment At Alternative and Bidirectional Promotersmentioning
confidence: 67%
“…Figure 2A presents the list of TFs with high percent of overlap with Z-flipons shared between human and mouse genomes. In line with our previous studies 23,26,27 we observed enrichment of Z-flipons in promoters. Since GC-repeats are prone to Z-formation we observe significant enrichment of Z-forming sequences in CpG-promoters.…”
Section: Conserved Patterns Of Transcription Factors and Histone Mark...supporting
confidence: 93%
“…Example of Wnt Family Member 5A (WNT5A) human and mouse genes with Z-flipons from the presynapse assembly pathway is given in Supplementary Figure 3. This gene harbors many Zflipons detected by three methods -DeepZ, experimental KEx permanganate/S1 nuclease detection method, 21 , and also with Z-DNABERT model 27 . Z-flipons in WNT5A gene are located in 5'UTR, near splice-sites, in exons, at alternative promoters.…”
Section: Clusters Of Common Conserved Z-flipons Between Human and Mou...mentioning
confidence: 99%
“…Large language models are the next generation predictive models that outperformed CNNs in many areas due to their ability to learn context. We previously applied DNABERT to reveal Z-DNA forming potential in human and mouse genomes 22 , and here we apply DNABERT to predict G4s. As the training set, we use Kouzine et al data set generated with permanganate/S1 Nuclease Footprinting methods 11 .…”
Section: Introductionmentioning
confidence: 99%